2021
DOI: 10.1186/s12913-021-07196-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the uptake of new medicines into clinical practice: a systematic review

Abstract: Background Implementation and uptake of novel and cost-effective medicines can improve patient health outcomes and healthcare efficiency. However, the uptake of new medicines into practice faces a wide range of obstacles. Earlier reviews provided insights into determinants for new medicine uptake (such as medicine, prescriber, patient, organization, and external environment factors). However, the methodological approaches used had limitations (e.g., single author, narrative review, narrow searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 94 publications
(457 reference statements)
3
37
0
Order By: Relevance
“…A recent systematic review of new drug uptake for, but not limited to, cancer drugs, summarized the influencing factors into broad categories of patient, prescriber, medicine, and organizational and environmental factors. 9 The geographic variation observed in our study could represent a combination of these factors. Additionally, the review found that the influence of each factor appeared to be different across drug types.…”
Section: Discussionmentioning
confidence: 74%
“…A recent systematic review of new drug uptake for, but not limited to, cancer drugs, summarized the influencing factors into broad categories of patient, prescriber, medicine, and organizational and environmental factors. 9 The geographic variation observed in our study could represent a combination of these factors. Additionally, the review found that the influence of each factor appeared to be different across drug types.…”
Section: Discussionmentioning
confidence: 74%
“…Previous research has grouped factors that influence implementation into patient, provider, innovation, structural and organizational factors (Chaudoir et al, 2013 ). For example, an efficacious intervention may fail in clinical practice because: the patient is an inappropriate fit, time constraints within the provider's role prevent adding or changing daily tasks and/or the organization culturally does not promote the use of a given intervention (Chaudoir et al, 2013 ; Medlinskiene et al, 2021 ). The multitude of factors contributing to sub-optimal implementation and the disproportional research focus on the external validity of interventions deeply impacts the adoption, sustainability, and scale-up of best practice evidence (Glasgow et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there are major breakthroughs in the understanding, investigation and treatments of common pleural diseases [ 6 ], which can reduce morbidity and improve quality of care for patients. However, the incorporation of major advances into clinical practice can vary tremendously across different healthcare systems [ 7 , 8 ], and there are a number of possible barriers contributing to the insufficient update and lack of implementation of guidelines and advances [ 9 ].…”
Section: Introductionmentioning
confidence: 99%